Proceedings of the 4th Annual International Conference on Management, Economics and Social Development (ICMESD 2018) 2018
DOI: 10.2991/icmesd-18.2018.150
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Cointegration between Services Exports and Economic Growth in Sri Lanka: Based on Nonlinear ARDL Model

Abstract: This study examines the asymmetric cointegration between services exports and economic growth in Sri Lanka. A nonlinear ARDL model is employed to analyze on the annual time series data over the period from 1984-2013.The results show that(1) ignorance of asymmetries between services exports and economic growth may lead towards misleading conclusions. (2) there is statistically significant difference in the response of economic growth to positive and negative shocks to the services exports both in long-and short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The study has engaged three co-integrating techniques non-linear autoregressive distributed lag (NARDL), Fully Modified Ordinary Least Squares (FMOLS), and Dynamic Ordinary Least Squares (DOLS) methods. The NARDL technique is best employed when there is a non-linear relationship among the variables in empirical analysis (Priyankara & Li, 2018), it has also been argued that the impact of the majority of the variables is non-linear (Esteve & Tamarit, 2012). Just like the traditional autoregressive distributed lag (ARDL), the NARDL can be employed regardless data series are purely co-integrated at levels or first difference, or as a mixture of both levels (Nkoro & Uko, 2016).…”
Section: Estimation Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The study has engaged three co-integrating techniques non-linear autoregressive distributed lag (NARDL), Fully Modified Ordinary Least Squares (FMOLS), and Dynamic Ordinary Least Squares (DOLS) methods. The NARDL technique is best employed when there is a non-linear relationship among the variables in empirical analysis (Priyankara & Li, 2018), it has also been argued that the impact of the majority of the variables is non-linear (Esteve & Tamarit, 2012). Just like the traditional autoregressive distributed lag (ARDL), the NARDL can be employed regardless data series are purely co-integrated at levels or first difference, or as a mixture of both levels (Nkoro & Uko, 2016).…”
Section: Estimation Techniquementioning
confidence: 99%
“…Also, it is observed that most of these studies engaged the bound cointegration test and the traditional Johansen co-integration test; which all assume a linear relationship among the variables of the regression model. However, most economic variables do not exhibit linear relationships instead, they are nonlinearly correlated (Priyankara & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation